2020
DOI: 10.1104/pp.20.00184
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Differences between the Tomato Immune Receptors Flagellin Sensing 3 and Flagellin Sensing 2

Abstract: Plants mount defense responses by recognizing indicators of pathogen invasion, including microbe-associated molecular patterns (MAMPs). Flagellin, from the bacterial pathogen Pseudomonas syringae pv. tomato (Pst), contains two MAMPs, flg22 and flgII-28, that are recognized by tomato (Solanum lycopersicum) receptors Flagellin sensing2 (Fls2) and Fls3, respectively, but to what degree each receptor contributes to immunity and whether they promote immune responses using the same molecular mechanisms are unknown. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 70 publications
(114 reference statements)
1
27
0
Order By: Relevance
“…To examine whether this is a general effect on PRRs, we tested whether CK influences the signaling of the LRR-receptor-like kinase (RLK)-type PRR FLS2. FLS2 is very different from LeEIX2 in its structure, specificity, and regulation [ 20 , 22 , 23 ]. Figure 1 demonstrates that CK affects cellular distribution of FLS2, increasing its presence at the PM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine whether this is a general effect on PRRs, we tested whether CK influences the signaling of the LRR-receptor-like kinase (RLK)-type PRR FLS2. FLS2 is very different from LeEIX2 in its structure, specificity, and regulation [ 20 , 22 , 23 ]. Figure 1 demonstrates that CK affects cellular distribution of FLS2, increasing its presence at the PM.…”
Section: Resultsmentioning
confidence: 99%
“…We have found that in addition to the xylanase receptor-like protein (RLP) LeEIX2, CK also affects the distribution of the flagellin receptor-like kinase (RLK) flagellin-sensing 2 (FLS2), increasing its presence in the plasma membrane. FLS2, first characterized in Arabidopsis, acts as the PRR for the bacterial PAMP (pathogen-associated molecular pattern) flagellin [ 22 ] in several plant species [ 23 , 24 , 25 ]. Furthermore, CK enhances the cellular response to the 22-amino-acid, flagellin-derived peptide flg22, and flg22 sensing activates the CK response.…”
Section: Introductionmentioning
confidence: 99%
“…This observation broadly corresponds with that reported for S. pimpinellifolium [ 5 ] and S. lycopersicum , cv. Rio Grande [ 29 ]. It appears that the FlgII-28 extended ROS response is conserved in all solanaceous species that respond to FlgII-28 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rio Grande [ 29 ]. It appears that the FlgII-28 extended ROS response is conserved in all solanaceous species that respond to FlgII-28 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation